Revisiting the Open Court Principle in an Era of Online Publication: Questioning Presumptive Public Access to Parties' and Witnesses' Personal Information - Bailey, Jane; Burkell, Jacquelyn (Ottawa Law Review, 2016)
Disclaimer: This summary was generated by AI based on the content of the source document.